Method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis

By using molten salt electrolysis and acid washing processes, lithium-based electrolytes are used to break down fluid inclusions in quartz sand under an electric field, solving the problems of low removal efficiency and high energy consumption in traditional methods. This achieves deep purification of high-purity quartz sand with a purity of over 99.998%.

CN122276764APending Publication Date: 2026-06-26HUBEI THREE GORGES LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610350077.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-20
Publication Date
2026-06-26

AI Technical Summary

Technical Problem

Existing technologies are ineffective at removing tiny fluid inclusions from quartz sand, resulting in low purity of high-purity quartz sand. Furthermore, traditional methods are energy-intensive and have low removal efficiency.

Method used

The process employs a combination of molten salt electrolysis and acid washing. Microcracks are generated by rapid cooling after high-temperature calcination. Electrolysis is then performed using a lithium-based electrolyte under an electric field. DC pulse voltage breaks down the inclusions, and impurities are thoroughly removed through mixed acid washing.

Benefits of technology

With low energy consumption, deep purification of quartz sand was achieved, with a purity of over 4N8, effectively removing tiny fluid inclusions and improving the quality of high-purity quartz sand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122276764A_ABST
    Figure CN122276764A_ABST
Patent Text Reader

Abstract

This invention discloses a method for deep removal of fluid inclusions from quartz sand using molten salt electrolysis, belonging to the field of quartz sand purification technology. This method uses vein quartz as raw material, which undergoes crushing, sieving, magnetic separation, and flotation followed by high-temperature calcination and ice-water quenching pretreatment to induce microcracks on the quartz sand surface. A molten salt electrolysis cell is then prepared under a dry nitrogen atmosphere using a nickel alloy as the cathode, graphite as the anode, and a lithium-based electrolyte salt as the electrolyte. The pretreated quartz sand is placed near the cathode and electrolyzed for 2-30 minutes using a 2-24V DC pulse voltage. The electric field causes dielectric breakdown and rupture of the fluid inclusions, driving the directional migration of impurity ions. Finally, the sand is washed with boiling water, leached with mixed acid, washed again, and dried to obtain high-purity quartz sand with a SiO2 purity of not less than 4N8. This invention solves the problem of removing tiny fluid inclusions using traditional methods through the synergistic effect of thermal explosion and molten salt electrolysis. It has low energy consumption, high purification effect, and the prepared high-purity quartz sand can meet the application needs of high-end industries such as semiconductors and photovoltaics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis, belonging to the technical field of quartz sand purification methods. Background Technology

[0002] There is no unified standard for high-purity quartz sand. Within the industry, quartz with a SiO2 purity of 99.99% or higher is generally referred to as high-purity quartz sand. High-purity quartz is an indispensable key material for strategic high-tech industries such as semiconductors, photovoltaics, precision optics, and fiber optic communications. In recent years, with the rapid development of emerging technology industries in my country, the demand for high-purity quartz has continued to grow, making China one of the world's major consuming countries.

[0003] High-purity quartz sand is obtained by continuously purifying quartz ore through multiple purification steps. Therefore, impurities and defects in the product originate from the raw quartz ore. Quartz ore is abundant worldwide, but due to differences in geological environments in different regions, the composition and occurrence forms of impurities in quartz ore vary significantly. Not all quartz ore can be processed into high-purity quartz sand; only a very small number of raw materials are truly suitable for producing high-purity quartz sand. In my country, high-purity quartz raw materials are mainly natural crystal and vein quartz. Natural crystal typically has a SiO2 content exceeding 99.9% and relatively low levels of impurity ions and fluid inclusions, making it relatively easy to obtain high-purity quartz sand through a series of steps. However, my country's natural crystal raw material mines are nearing depletion, and currently, vein quartz is generally the main raw material. However, vein quartz contains more fluid inclusions, and most impurity elements are hidden within these inclusions. These inclusions are difficult to remove because they are located inside the quartz sand, and their presence has a significant negative impact on product performance.

[0004] The key to mastering high-end quartz products lies in removing fluid inclusions. Currently, the domestic method generally employs thermal detonation to minimize inclusions. This involves heating the quartz sand to extremely high temperatures, causing the inclusions to rupture due to the significant pressure difference between the inside and outside of the inclusions. Rapid cooling then exposes the inclusions by completely breaking them apart through the large temperature difference. Finally, a series of acid washing processes remove the inclusions and internal impurities. However, the removal effect is closely related to the size and shape of the quartz particles. For fluid inclusions with large aspect ratios, the stress generated by detonation can effectively "open" them, but it is difficult to destroy the small inclusions. Directly melting the quartz sand requires heating to over 1700°C, resulting in extremely high energy consumption, and the molten quartz sand has extremely high viscosity, making it difficult to process. Summary of the Invention

[0005] To address the problems existing in the prior art, this invention provides a method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis, which solves the problems of poor inclusion removal effect and low removal efficiency in the prior art. Combined with acid washing process, the final high-purity quartz sand prepared has a purity of 4N8 or higher.

[0006] To achieve the above technical objectives, the present invention adopts the following technical solution:

[0007] A method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis includes the following steps performed sequentially: 1) Pretreatment: After calcination, the quartz sand is rapidly cooled in a cooling liquid while still hot, then filtered and dried to obtain pretreated quartz sand; 2) Electrolytic cell preparation: Using nickel alloy as cathode and graphite as anode, the electrodes are inserted into an electrolytic cell containing electrolyte. The electrolytic cell is heated to the temperature at which the electrolyte melts under an inert atmosphere to obtain a molten salt electrolytic cell. 3) Molten salt electrolysis: The pretreated quartz sand is encapsulated in a conductive screen and placed near the cathode of the molten salt electrolysis cell. A DC pulse voltage is applied for electrolysis. After electrolysis is completed, the quartz sand is removed. 4) Acid leaching purification: The electrolyzed quartz sand is sequentially washed with water to remove electrolyte, acid washed to remove impurities, and washed with water and dried to obtain high-purity quartz sand.

[0008] Through the above technical steps, the quartz sand is first calcined at high temperature and held at that temperature for a certain period of time to ensure that the heat penetrates into the fluid inclusions. Then, the high-temperature quartz sand is poured into a cooling liquid for rapid cooling and water quenching. Rapid thermal expansion and contraction create cracks on the quartz surface. After drying, it is placed in an electrolytic cell containing molten electrolyte for further dissociation of inclusion impurities. The quartz sand and molten salt form a conductive ionic melt. When a DC pulse current is passed through the cracked quartz sand particles, the current is highly concentrated within the inclusions due to the presence of inclusions inside the cracks. The heat generated per unit volume is much higher than in other intact areas, causing the inclusions to expand violently and burst. Simultaneously, under the action of an external electric field, impurity ions in the inclusions and in the quartz sand lattice migrate directionally towards the cathode, gaining electrons and being reduced to metal atoms or forming alloys, which are then deposited on the cathode surface or at the bottom of the melt. After electrolysis, the entrained electrolyte salts are first removed by washing with water. There may still be inclusions in the quartz sand that have burst open but have not migrated under the action of the electric field. These are then further removed by acid washing.

[0009] Preferably, the quartz sand raw material in step 1) is vein quartz, which is obtained by crushing, magnetic separation and flotation.

[0010] The quartz ore is crushed and then screened to obtain quartz sand with a particle size of 50-150 mesh.

[0011] Through the above technical steps, the particle size range of quartz sand was defined, and the associated impurities and non-structural impurities carried by quartz ore were initially removed.

[0012] Preferably, the high-temperature calcination temperature in step 1) is 1000~1500 ℃, the holding time is 10~60 min, and the coolant is ice water.

[0013] Through the above technical steps, high-temperature quartz sand is rapidly immersed in the cooling liquid. The quartz crystal skeleton shrinks due to rapid cooling, but the fluid inside the inclusion does not have time to shrink, which will generate huge tensile stress on the inclusion wall. The drastic change of high stability and rapid cooling causes micron / nano-scale microcracks to be generated in the inclusion wall leading to the outside of the quartz, creating a crucial channel for the subsequent penetration of molten salt electrolyte into the inclusion.

[0014] The electrolyte is a lithium-based electrolyte salt, and the melting temperature of the electrolyte is 200~1000℃; the inert atmosphere is dry nitrogen.

[0015] The melting temperature refers to the melting temperature at which different electrolyte salts are obtained. The lithium-based electrolyte salts include at least one or more of lithium hexafluorophosphate, lithium difluorooxalate borate, lithium difluorophosphate, lithium thiophosphate, lithium aluminum titanium phosphate, and lithium phosphorus sulfur chloride.

[0016] Through the above technical steps, lithium-based electrolyte salts are used, which are excellent lithium-ion conductors. They exhibit stable melt structures at high temperatures, have a wide electrochemical window, and can form molten salt systems with lower melting points and better fluidity. This allows for purification at lower temperatures, reducing energy consumption and equipment corrosion. Furthermore, lithium ions (Li... + With its extremely small radius, it possesses exceptionally strong diffusion and penetration capabilities in its high-temperature molten state, making it easier to penetrate into the microcracks and inclusion interfaces of quartz sand, enabling "inside-out" chemical or electrochemical stripping of internal impurities. After high-temperature decomposition or melting of lithium difluorophosphate, lithium thiophosphate, lithium phosphorus sulfide, and chlorine, the resulting phosphorus oxides and sulfides may react with specific metallic impurities in quartz (such as iron, aluminum, and titanium) to form water-soluble phosphates or sulfides, achieving deep removal.

[0017] Preferably, the electrolysis process described in step 3) is carried out in a dry nitrogen atmosphere.

[0018] The above technical steps create an inert gas atmosphere to prevent oxygen and moisture in the air from reacting with the electrodes, molten salt, or quartz sand at high temperatures.

[0019] Preferably, the screen in step 3) is made of 200-mesh nickel alloy, the quartz sand is placed in the mesh bag and placed near the cathode, the DC pulse voltage applied during electrolysis is in the range of 2~24 V, and the electrolysis time is 2~30 min.

[0020] Through the above technical steps, the quartz sand is encapsulated for easy removal and solid-liquid separation from the molten salt. The nickel mesh itself acts as an extension of the cathode, ensuring that all quartz sand particles are within the cathode electric field environment. When the molten salt electrolyte penetrates into the inclusion through microcracks, the interior of the inclusion is also filled with conductive electrolyte, forming a miniature "internal electrolytic cell." The pulsed voltage has higher peak power and stronger penetration capability. Under the action of the high-voltage pulse, the inclusion wall, which acts as the "dielectric layer" between the internal electrolyte and the external molten salt, will instantly undergo high-voltage dielectric breakdown, causing physical rupture. After breakdown, impurity ions within the inclusion rapidly migrate to the cathode under the influence of the electric field and are reduced or fixed, while internal anions migrate to the anode, driving the migration of impurities within the crystal lattice under the influence of the strong electric field.

[0021] Preferably, the water washing in step 4) is performed in boiling water.

[0022] Through the above technical steps, the electrolytes are all water-soluble, and the electrolyte salts carried during the electrolysis process can be quickly washed away by washing in boiling water.

[0023] Preferably, the acid in step 4) is one or more of hydrofluoric acid, hydrochloric acid, sulfuric acid or nitric acid, the concentration of hydrofluoric acid is 1~5 wt%, the concentration of hydrochloric acid is 5~15 wt%, the concentration of sulfuric acid is 0~1 wt%, the concentration of nitric acid is 0~1 wt%, the solid-liquid ratio of quartz sand to acid in the pickling process is 1:(1~5), the pickling temperature is 50~200℃, and the pickling time is 1~8 h.

[0024] Through the above technical steps, hydrofluoric acid can react with quartz sand, and by slightly corroding the quartz surface and crack channels, it can completely dissolve and wash out the broken but not completely detached inclusion wall remnants and exposed solid impurities (such as microcrystals and altered minerals). The mixed acid combination of hydrochloric acid, sulfuric acid or nitric acid can enhance the dissolution ability of various impurities, and under heating conditions, it can accelerate the movement of molecules, which helps the acid to penetrate into the crack channels and dissolve inclusion impurities. Attached Figure Description

[0025] The accompanying drawings, which form part of this specification, illustrate embodiments of the invention and, together with the specification, serve to explain the principles of the invention.

[0026] Figure 1 The image shows the high-purity quartz sand prepared in Example 1 under a polarizing microscope.

[0027] Figure 2 Image of the high-purity quartz sand prepared for Comparative Example 1 under a polarizing microscope.

[0028] Figure 3 The image shows the high-purity quartz sand prepared for Comparative Example 2 under a polarizing microscope. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] The quartz sand raw materials used in the following embodiments were obtained by crushing, magnetic separation, and flotation, and the impurity content was analyzed. The test results are shown in Table 1.

[0031] Table 1

[0032] Example 1 A method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis includes the following steps: The vein quartz ore was crushed and sieved to obtain quartz sand of 50-150 mesh. After magnetic separation and flotation, the sand was placed in a crucible and calcined at 1200 ℃ for 30 min. The sand was then removed at high temperature and poured into ice water for rapid cooling. Nickel alloy electrodes and graphite electrodes were used as the cathode and anode electrodes of the electrolytic cell, respectively. Lithium hexafluorophosphate electrolyte was added and heated to 300 ℃ to melt the electrolyte. The quartz sand was scooped out, washed and dried, then wrapped in a 200-mesh nickel alloy sieve and immersed in an electrolytic cell. It was placed near the cathode electrode and a 10 V DC pulse voltage was applied. Electrolysis was carried out at this voltage for 20 min. After electrolysis, the sieve containing the quartz sand was removed and directly immersed in boiling water to wash away the entrained electrolyte. After drying, hydrofluoric acid (2 wt%), hydrochloric acid (15 wt%), and sulfuric acid (1 wt%) were added at a solid-liquid ratio of 1:1. The mixture was then acid-leached in a closed reactor at 200 °C for 5 h. Finally, it was washed with water and dried to obtain high-purity quartz sand. After digestion, the purity of SiO2 was analyzed by ICP.

[0033] Example 2 A method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis includes the following steps: The raw quartz ore was crushed and sieved to obtain quartz sand of 50-150 mesh. After magnetic separation and flotation, the sand was placed in a crucible and calcined at 1500 °C for 20 min. The calcined sand was then removed at high temperature and rapidly cooled in ice water. Nickel alloy and graphite electrodes were used as the cathode and anode electrodes of the electrolytic cell, respectively. Lithium difluorooxalate-borate electrolyte was added and heated to 320 °C to melt the electrolyte. The quartz sand was then removed, washed, and dried. It was then wrapped in a 200-mesh nickel alloy sieve and immersed in the electrolytic cell, placed near the cathode electrode. A 20 V DC pulse voltage was applied, and electrolysis was performed for 2 min at this voltage. After electrolysis, the sieve containing the quartz sand was removed and directly immersed in boiling water to remove any entrained electrolyte. After drying, hydrofluoric acid (5 wt%) and hydrochloric acid (10 wt%) were added at a solid-liquid ratio of 1:2. The mixture was then acid-leached at 100 °C for 3 minutes in a closed reactor. h, finally washed and dried to obtain high-purity quartz sand, which was then digested and subjected to ICP analysis for SiO2 purity.

[0034] Example 3 A method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis includes the following steps: The raw quartz ore was crushed and sieved to obtain quartz sand of 50-150 mesh. After magnetic separation and flotation, the sand was placed in a crucible and calcined at 1000 °C for 10 min. The calcined sand was then removed at high temperature and quenched in ice water. Nickel alloy and graphite electrodes were used as the cathode and anode electrodes of the electrolytic cell, respectively. Lithium difluorophosphate was added, and the mixture was heated to 420 °C to melt the electrolyte. The quartz sand was removed, washed, and dried. It was then wrapped in a 200-mesh nickel alloy sieve and immersed in the electrolytic cell, placed near the cathode electrode. A 15 V DC pulse voltage was applied, and electrolysis was performed for 10 min at this voltage. After electrolysis, the sieve containing the quartz sand was removed and directly immersed in boiling water to remove any entrained electrolyte. After drying, a mixture of 1 wt% hydrofluoric acid, 10 wt% hydrochloric acid, 1 wt% sulfuric acid, and 1 wt% nitric acid was added at a solid-liquid ratio of 1:3. The mixture was then acid-leached at 150 °C in a sealed reactor. h, finally washed and dried to obtain high-purity quartz sand, which was then digested and subjected to ICP analysis for SiO2 purity.

[0035] Example 4 A method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis includes the following steps: The raw quartz ore was crushed and sieved to obtain quartz sand of 50-150 mesh. After magnetic separation and flotation, the sand was placed in a crucible and calcined at 1100 °C for 50 min. The calcined sand was then removed at high temperature and quenched in ice water. Nickel alloy and graphite electrodes were used as the cathode and anode electrodes of the electrolytic cell, respectively. Lithium thiophosphate was added, and the mixture was heated to 650 °C to melt the electrolyte. The quartz sand was then removed, washed, and dried. It was then wrapped in a 200-mesh nickel alloy sieve and immersed in the electrolytic cell, placed near the cathode electrode. A 2 V DC pulse voltage was applied, and electrolysis was performed for 30 min at this voltage. After electrolysis, the sieve containing the quartz sand was removed and directly immersed in boiling water to remove any entrained electrolyte. After drying, a mixture of 4 wt% hydrofluoric acid, 12 wt% hydrochloric acid, 1 wt% sulfuric acid, and 1 wt% nitric acid was added at a solid-liquid ratio of 1:4. The mixture was then acid-leached at 50 °C for 6 minutes in a sealed reactor. h, finally washed and dried to obtain high-purity quartz sand, which was then digested and subjected to ICP analysis for SiO2 purity.

[0036] Example 5 A method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis includes the following steps: The raw quartz ore was crushed and sieved to obtain quartz sand of 50-150 mesh. After magnetic separation and flotation, the sand was placed in a crucible and calcined at 1400 °C for 60 min. The calcined sand was then removed at high temperature and quenched in ice water. Nickel alloy and graphite electrodes were used as the cathode and anode electrodes of the electrolytic cell, respectively. Lithium aluminum titanium phosphate was added, and the mixture was heated to 800 °C to melt the electrolyte. The quartz sand was then removed, washed, and dried. It was then wrapped in a 200-mesh nickel alloy sieve and immersed in the electrolytic cell, placed near the cathode electrode. A 24 V DC pulse voltage was applied, and electrolysis was performed for 15 min at this voltage. After electrolysis, the sieve containing the quartz sand was removed and directly immersed in boiling water to remove any entrained electrolyte. After drying, 5 wt% hydrofluoric acid and 5 wt% hydrochloric acid were added at a solid-liquid ratio of 1:5. The mixture was then acid-leached at 200 °C for 8 minutes in a sealed reactor. h, finally washed and dried to obtain high-purity quartz sand, which was then digested and subjected to ICP analysis for SiO2 purity.

[0037] Comparative Example 1 A method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis includes the following steps: The vein quartz ore was crushed and sieved to obtain quartz sand of 50-150 mesh. After magnetic separation and flotation, the sand was placed in a crucible and calcined at 1200 ℃ for 30 min. The calcined sand was then removed at high temperature and poured into ice water for rapid cooling. After drying, hydrofluoric acid (2 wt%), hydrochloric acid (15 wt%), and sulfuric acid (1 wt%) were added at a solid-liquid ratio of 1:1. The mixture was then acid-leached at 200 ℃ for 5 h in a closed reactor. Finally, the sand was washed with water and dried to obtain high-purity quartz sand. After digestion, the purity of SiO2 was analyzed by ICP.

[0038] Comparative Example 2 A method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis includes the following steps: The raw quartz ore was crushed and sieved to obtain quartz sand of 50-150 mesh. After magnetic separation and flotation, the sand was placed in a crucible and calcined at 1200 °C for 30 min. The calcined sand was then removed at high temperature and quenched in ice water. Nickel alloy and graphite electrodes were used as the cathode and anode electrodes of the electrolytic cell, respectively. A calcium chloride and sodium chloride electrolyte with a mass ratio of 1:5 was prepared and heated to 600 °C to melt the electrolyte. The quartz sand was then removed, washed, and dried. It was then wrapped in a 200-mesh nickel alloy sieve and immersed in the electrolytic cell, placed near the cathode electrode. A 10 V DC pulse voltage was applied, and electrolysis was performed for 20 min at this voltage. After electrolysis, the sieve containing the quartz sand was removed and directly immersed in boiling water to remove any entrained electrolyte. After drying, a mixture of 2 wt% hydrofluoric acid, 15 wt% hydrochloric acid, and 1 wt% sulfuric acid was added at a solid-liquid ratio of 1:1. The mixture was then acid-leached at 200 °C for 5 minutes in a sealed reactor. h, finally washed and dried to obtain high-purity quartz sand, which was then digested and subjected to ICP analysis for SiO2 purity.

[0039] The purified quartz sand prepared in the examples was analyzed and tested according to the method in GB / T 3284-2015. The test results are shown in Table 2.

[0040] Table 2

[0041] from Figure 1 , 2 As shown in Figure 3, the sample subjected to molten salt electrolysis exhibits better light transmittance under a polarizing microscope, indicating that it has achieved the effect of destroying or removing inclusions inside the quartz sand. Figure 2 The image of the high-purity quartz sand prepared in Comparative Example 1 under a polarizing microscope shows that calcination and acid leaching alone cannot achieve deep removal, resulting in a darker appearance under the microscope. This is due to the difference in conductivity between the molten salt electrolyte used in the electrolysis process. Figure 1Using lithium-based electrolyte salts, which have better penetration capabilities in the molten state, they can more easily penetrate into the microcracks and inclusion interfaces of quartz sand to chemically or electrochemically remove internal impurities. Figure 3 The image shows the high-purity quartz sand prepared in Comparative Example 2 under a polarizing microscope. Under the same electrolysis conditions, calcium chloride and sodium chloride have narrower electrochemical windows than lithium-based electrolytes, and also differ in ion mobility and conductivity, exhibiting greater resistance to impurity migration.

[0042] As shown in Table 2, this invention first subjects the quartz sand to a thermal explosion pretreatment involving high-temperature calcination followed by rapid cooling, inducing microcracks within the sand. Subsequently, under an inert atmosphere, electrolysis is performed using nickel alloy and graphite electrodes in a lithium-based electrolyte system with a DC pulse voltage. The electric field causes dielectric breakdown of the inclusions, driving impurity ions to migrate towards the cathode. Finally, residual impurities are thoroughly removed through mixed acid washing. The synergistic effect of thermal explosion and electrolysis effectively solves the problem of traditional methods' difficulty in deeply removing micro-fluid inclusions. This allows for the purification of vein quartz raw materials to high-purity quartz sand with a purity exceeding 99.998% with relatively low energy consumption, providing a key material preparation technology for high-end industries such as semiconductors and photovoltaics.

[0043] The above description is merely an embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the scope of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for deep removal of fluid inclusions in quartz sand by molten salt electrolysis, characterized in that, Includes the following steps: 1) Pretreatment: After calcination, the quartz sand is rapidly cooled in a cooling liquid while still hot, then filtered and dried to obtain pretreated quartz sand; 2) Electrolytic cell preparation: Using nickel alloy as cathode and graphite as anode, the electrodes are inserted into an electrolytic cell containing electrolyte. The electrolytic cell is heated to the temperature at which the electrolyte melts under an inert atmosphere to obtain a molten salt electrolytic cell. 3) Molten salt electrolysis: The pretreated quartz sand is encapsulated in a conductive screen and placed near the cathode of the molten salt electrolysis cell. A DC pulse voltage is applied for electrolysis. After electrolysis is completed, the quartz sand is removed. 4) Acid leaching purification: The electrolyzed quartz sand is sequentially washed with water to remove electrolyte, acid washed to remove impurities, and washed with water and dried to obtain high-purity quartz sand.

2. The method according to claim 1, characterized in that, The quartz sand mentioned in step 1) is the product of vein quartz after crushing, screening, magnetic separation and flotation, and the particle size of the quartz sand is 50~150 mesh.

3. The method according to claim 1, characterized in that, The calcination temperature in step 1) is 1000~1500℃, and the holding time is 10~60min; the cooling liquid is ice water, and the calcination is carried out in a high-temperature muffle furnace.

4. The method according to claim 1, characterized in that, The electrolyte in step 2) is a lithium-based electrolyte salt, and the melting temperature of the electrolyte is 200~1000℃; the inert atmosphere is dry nitrogen.

5. The method according to claim 1, characterized in that, The lithium-based electrolyte salts include at least one or more of lithium hexafluorophosphate, lithium difluorooxalate borate, lithium difluorophosphate, lithium thiophosphate, lithium aluminum titanium phosphate, and lithium phosphorus sulfur chloride.

6. The method according to claim 1, characterized in that, The conductive screen mentioned in step 3) is a nickel alloy screen with a mesh size of 200; the DC pulse voltage range is 2~24V, the electrolysis time is 2~30min, and the quartz sand is completely immersed in the molten electrolyte during the electrolysis process.

7. The method according to claim 1, characterized in that, In the molten salt electrolysis process, electrolyte ions penetrate into the fluid inclusions through the microcracks in the pretreated quartz sand, forming an internal conductive system. The DC pulse voltage causes dielectric breakdown of the inclusion wall, and impurity ions migrate directionally towards the cathode under the action of the electric field. Some impurity ions are reduced to metal atoms or form alloys that are deposited on the cathode surface.

8. The method according to claim 1, characterized in that, The water washing described in step 4) is boiling water washing, and the washing time is based on removing all electrolytes from the surface and pores of the quartz sand.

9. The method according to claim 1, characterized in that, The acid used in step 4) for pickling is one or a mixture of hydrofluoric acid, hydrochloric acid, sulfuric acid, and nitric acid; wherein the mass concentration of hydrofluoric acid is 1~5wt%, the mass concentration of hydrochloric acid is 5~15wt%, the mass concentration of sulfuric acid is 0~1wt%, and the mass concentration of nitric acid is 0~1wt%; the process parameters for pickling are: the solid-liquid ratio of quartz sand to acid is 1:(1~5), the pickling temperature is 50~200℃, and the pickling time is 1~8h.

10. The method according to claim 1, characterized in that, The SiO2 purity of the high-purity quartz sand is not less than 99.998%.